Evaluation of the Accuracy of Working Casts Fabricated by Four Implant Impression Techniques in Parallel and Nonparallel Implant Configurations - Jaghsi, Ahmad Al; Rokaya, Dinesh (European Journal of Dentistry, 2025)
The implant impression technique plays a critical role in determining the accuracy of implant working casts. This laboratory study aimed to evaluate and compare the accuracy of working casts fabricated using four different impression techniques in both parallel and nonparallel implant configurations.An aluminum master model was made to simulate a mandibular dental arch. Impressions of the dental implants were made using four techniques within an incubator: (A) unsplinted tapered impression copings; (B) unsplinted squared impression copings; (C) splinted squared impression copings with dental floss supported with self-curing acrylic resin; and (D) splinted squared impression copings with prefabricated self-curing acrylic resin bars. Measurements were made using a universal measuring microscope in the x- and y-dimensions. The mean deviation index was calculated and compared. Statistical analysis was done using SPSS version 23. Comparisons of the distance deviation index in various groups were conducted using one-way analysis of variance. Furthermore, comparisons of the distance deviation index in nonparallel implants in various techniques were performed using the independent t-test. A p-value of 0.05 was considered a significant difference.For the parallel implants, the distance deviation index difference between the techniques was not significant. In the case of nonparallel implants, there was statistically significant difference only between the technique C versus technique D (p =  0.019). All the impression techniques showed statistically significant differences between parallel versus nonparallel implant placement in favor of the parallel. Overall, technique D demonstrated the best results for both parallel and nonparallel implant placements when compared with other techniques under the same conditions.The impression technique affects the accuracy of the implant impression. Within the limitations of this study, impression transfer copings splinted with dental floss and reinforced with self-cure acrylic resin are not recommended, particularly when the implants are not parallel. In the case of parallel implants, there appears to be no statistically significant benefit from splinting transfer impression copings.
Keywords: dental implants; implant impressions; parallel implants; nonparallel implants